2008
DOI: 10.1021/ja710664y
|View full text |Cite
|
Sign up to set email alerts
|

Planar Meso Pentafluorophenyl Core Modified Isophlorins

Abstract: Isophlorins and its analogues bridge the structural features between porphyrins and annulenes. Invariably they are known to be unstable but can be stabilized by appropriate substituents in the core and periphery of a macrocycle. Solid-state characterization of these 20pi systems displays planarity for each macrocycle and even in their supramolecular arrangement due to C-H...F-C interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 13 publications
3
81
0
1
Order By: Relevance
“…By contrast, Setsune's N 21 ,N 22 -bridged N 4 -isophlorins are not highly deviated from planarity and exhibit paratropic ring current effects in the 1 H NMR spectra [17]. Anand's core-modified O 4 -and O 2 ,S 2 -isophlorins bearing meso-pentafluorophenyl groups have a completely planar structure and display antiaromatic character [18]. In addition to these isophlorin free bases, a few TPP-type metal-N 4 -isophlorin complexes have recently been characterized by spectroscopy and/or X-ray crystallography [19,20].…”
Section: Crystal Structuresmentioning
confidence: 96%
“…By contrast, Setsune's N 21 ,N 22 -bridged N 4 -isophlorins are not highly deviated from planarity and exhibit paratropic ring current effects in the 1 H NMR spectra [17]. Anand's core-modified O 4 -and O 2 ,S 2 -isophlorins bearing meso-pentafluorophenyl groups have a completely planar structure and display antiaromatic character [18]. In addition to these isophlorin free bases, a few TPP-type metal-N 4 -isophlorin complexes have recently been characterized by spectroscopy and/or X-ray crystallography [19,20].…”
Section: Crystal Structuresmentioning
confidence: 96%
“…It was also observed that 7 exhibited significant emission at l = 410 and 434 nm when excited either at l = 360 or 370 nm, with aq uantum yield (F)o f2 .2 %i nd ichloromethane,a nd 10 displayed aweak (F = 1.2) but strong red-shifted emission at l = 650 nm, which is very much similar to that observed for tetraphenyl porphyrins.C yclic voltammetry studies revealed two reversible reductions and oxidations,w ith a D redox of 1.18 V. More significantly, 7 displayed ar elatively lower oxidation potential compared to that of the tetraphenyl porphyrin and meso-tetra(pentafluorophenyl)teraoxaisophlorin. [3] These lower oxidation values were found to be quasireversible in nature.Inanattempt to reduce the dication to the 20p antiaromatic isophlorin, 10 was treated with reducing agents such as FeCl 2 and sodium. Neither of them yielded 7.However,itcould be reduced to 7 by the addition of zinc dust.…”
Section: Angewandte Chemiementioning
confidence: 92%
“…[1] Donor atoms such as OorS or Se in core-modified porphyrins alter the ligating properties while sustaining the structural features and electronic properties of the parent macrocycle.H owever,r eplacement of all four pyrroles by other heterocyclic units in aporphyrin yields antiaromatic 20p isophlorins (4 and 5)with similar structural characteristics but altered electronic properties. [2,3] As ignificant difference between porphyrin and isophlorin is observed in their reactivity towards protic acids.2 0 p isophlorins are characteristic organic molecules with pseudometal properties. [4] Thec ompounds 4 and 5 undergo two-electron ring oxidation to yield the 18p aromatic dication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H NMR (500 MHz, (CD 3 ) 2 CO, 175 K): d = 12.83(d, 2 H, 16 Hz), 5.98 (d, 2 H, 4 Hz), 6 H), 5.51 (d, 2 H, 4 Hz), 5.42 (d, 2 H, 4 Hz), 5.37 ppm 1 H NMR (500 MHz, (CD 3 ) 2 CO, 175 K): d = 12.83(d, 2 H, 16 Hz), 5.98 (d, 2 H, 4 Hz), 6 H), 5.51 (d, 2 H, 4 Hz), 5.42 (d, 2 H, 4 Hz), 5.37 ppm…”
unclassified